The Influence of Organizational Culture and Motivation on Employee Performance in The Rubber Department at Pt Adis Dimension Footwear Tangerang Regency - Aziizi, Muhammad Nur; Yulandari, Sri; Setiawan, Temmy (IJOSPOL - International Journal of Social, Policy and Law, 2026)
This study aims to determine: (1) the partial effect of organizational culture on employee performance; (2) the partial effect of motivation on employee performance; (3) the simultaneous effect of organizational culture and work motivation on employee performance.This study used a quantitative descriptive method, which describes variables as they are, supported by numerical data generated from actual conditions. The population in this study was all employees at PT. Adis Dimension Footwear Balaraja-Tangerang. The research sample consisted of 65 respondents. This study used a saturated sampling technique due to the small population size; therefore, the sample in this study used the entire population, 84 employees, as respondents. Data collection techniques used were observation, questionnaires, and documentation. Data analysis used multiple linear regression analysis with SPSS 26. Data validity was obtained through a partial t-test and a simultaneous F-test.The results of this study indicate that (1) partially, organizational culture significantly influences the performance of employees in the Rubber division at PT. Adis Dimension Footwear Balaraja-Tangerang, which is indicated by the calculated t value > t table (5.847 >1.999) and the significance value of 0.000 is smaller than the significance value of 0.05. Thus Ha is accepted and H0 is rejected. (2) Partially, motivation significantly influences the performance of Rubber department employees at PT. Adis Dimension Footwear Balaraja-Tangerang, which is indicated by the calculated t value > t table (2.129 >1.999) and the significance value of 0.000 is smaller than the significance value of 0.05. Thus Ha is accepted and H0 is rejected. (3) Simultaneously, organizational culture and motivation significantly influence the performance of Rubber department employees at PT. Adis Dimension Footwear Balaraja-Tangerang, which is indicated by the calculated F value > F table (58.518 >3.15) with a significance level of 0.000. Thus Ha is accepted and H0 is rejected. Based on the research results, it can be concluded that organizational culture and motivation variables, both partially and simultaneously, have a significant influence on the performance of Rubber department employees at PT. Adis Dimension Footwear Balaraja-Tangerang.